Study of Cauje (Pouteria caimito) as a gastronomic nutritional food in school children from 6 to 12 years of age at the "León de Febres Cordero" school in the city of Guayaquil. - Gordillo Alvarado, Mercedes María (Ingeniería Química y Desarrollo, 2023)
The present work is a compilation of information about caimito pouteria, and its subsequent introduction in the daily diet of schoolchildren between 6 and 12 years of a fiscal school located in the city of Guayaquil, in our city there are high indicators of malnutrition or obesity whose origin begins with poor diet which is generated by excessive consumption of fats and carbohydrates mainly in children 9 to 11 years of age, while malnutrition is especially due to lack of intake of micronutrients and is more common in younger children 5 years. Ecuador is a country with a diversity of fruits with a high nutritional potential which unfortunately is unknown to many Ecuadorian families, among them we have the channel (Pouteria caimito) that contains a great variety of vitamins that contribute a lot to the immune system in addition to a high presence Calcium, Phosphorus and Lysine which is one of the 10 essential amino acids for humans, in addition to its consumption stimulates growth hormone and mental development, taking into account all the nutritional benefits that the fruit contains, I conduct a research study which includes the realization of gastronomic proposals to be included in the daily school diet of children of the "Leon de Febres Cordero" School, carrying out periodic monitoring of their evolution in height and weight. For 2 months, the records are attached and the change obtained in the infants can be evidenced.